Some Important Aspects of Post-Classical Islamic Historiography Based on the Existing Western Scholarship - Safari, Safari (Paramita: Historical Studies Journal, 2023)
Most existing studies on Islamic historiography are dominated by the study of the classical-formative period (7th-9th Centuries AD). In contrast, the works in the later/post-classical period still need to be studied so that it becomes an important issue to be addressed. This paper seeks to review the existing scholarship on Islamic historiography in the context of the post-classical period (9th century onwards). This research addresses the discourse developed in studying Islamic historiography during this period by examining the historiographical characteristics and historical context. The findings in this article are based on library research that examines existing studies on Islamic historiography in Western scholarship with intellectual history as the theoretical framework for analyzing the data. The results of this study show that the existing studies, since H.A.R. Gibb, Franz Rosenthal, to Tarif Khalidi, have successfully established the classical period of Islamic historiography. In contrast, the study on “the later period” still needs attention. Chase F. Robinson is the most recent scholar who began paying attention to this period. His initial investigations showed the specific characteristics of this period: the distancing from traditionalist culture, the elimination of the use of isnad in writing history, the three main formats in historical writing (chronography, biography, and prosopography), and the emergence of a critical historical school that made history an independent official discipline. This article will conclude, in the end, with a reflection on some of the remaining lacunas in this area of research, along with a brief note on the Indonesian context, both as part of the analytical category in the study and concerning the analysis of Islamic history in that country.    Keywords: Islamic Historiography, Western Scholarship, The Post-Classical PeriodMayoritas kajian dalam historiografi Islam yang ada didominasi oleh telaah di masa klasik-formatif (7th-9th Centuries AD) dan khazanah setelahnya mayoritas masih belum dikaji, sehingga menjadi isu yang penting untuk diperhatikan. Tulisan ini berupaya untuk mereviu perkembangan kesarjanaan historiografi Islam di Barat dalam konteks pasca klasik (Abad ke-9 dan seterusnya). Temuan dalam artikel ini didasarkan kepada penelitian kepustakaan yang menelaah kajian-kajian yang ada tentang historiografi Islam di kesarjanaan barat dengan lensa sejarah intelektual sebagia acuan analisis data. Hasil penelitian menunjukkan bahwa kajian yang ada saat ini, sejak H.A.R. Gibb, Franz Rosenthal, hingga Tarif Khalidi, telah berhasil memetakan periode klasik historiografi Islam. Adapun kajian terhadap period berikutnya masih perlu mendapatkan perhatian. Chase F. Robinson adalah sarjana terkini yang mulai melakukan telaah atas periode tersebut. studi awal yang ia lakukan menunjukkan adanya karakteristik khusus di periode ini;  penarikan jarak dari kultur tradisionalis, eliminasi penggunaan isnād dalam menulis sejarah, tiga format utama dalam tulisan sejarah (kronografi, biografi, dan prosopografi) serta munculnya aliran sejarah kritis yang menjadikan sejarah sebagai disiplin resmi yang independen. Artikel ini akan diakhiri dengan refleksi terkait beberapa lacunas yang masih tersisa dalam area riset ini, berikut catatan singkat terkait konteks Indonesia, baik sebagai kategori analitis dalam kerja riset dan catatan atas fenomena riset sejarah Islam di negara ini.      Kata kunci: Historiografi Islam, Kesarjanaan Barat, Periode Pasca Klasik